2015
DOI: 10.5966/sctm.2014-0275
|View full text |Cite
|
Sign up to set email alerts
|

A Universal and Robust Integrated Platform for the Scalable Production of Human Cardiomyocytes From Pluripotent Stem Cells

Abstract: Recent advances in the generation of cardiomyocytes (CMs) from human pluripotent stem cells (hPSCs), in conjunction with the promising outcomes from preclinical and clinical studies, have raised new hopes for cardiac cell therapy. We report the development of a scalable, robust, and integrated differentiation platform for large-scale production of hPSC-CM aggregates in a stirred suspension bioreactor as a single-unit operation. Precise modulation of the differentiation process by small molecule activation of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 52 publications
(82 reference statements)
3
93
0
Order By: Relevance
“…Labeled exosomes were washed with PBS and ultracentrifuged at 100 000 g for 100 min (Type 45 Ti rotor, 30 000 rpm, k‐factor 133, Beckman coulter, L‐100XP ultracentrifuge). PKH26‐labeled exosomes (10 µg/mL) were co‐cultured with human embryonic stem cell derived cardiomyocytes (hESC‐CMs) for 2 h. hESC‐CMs were obtained according to a previously described protocol . Exosome uptake by the hESC‐CMs was stopped by washing with cold PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Labeled exosomes were washed with PBS and ultracentrifuged at 100 000 g for 100 min (Type 45 Ti rotor, 30 000 rpm, k‐factor 133, Beckman coulter, L‐100XP ultracentrifuge). PKH26‐labeled exosomes (10 µg/mL) were co‐cultured with human embryonic stem cell derived cardiomyocytes (hESC‐CMs) for 2 h. hESC‐CMs were obtained according to a previously described protocol . Exosome uptake by the hESC‐CMs was stopped by washing with cold PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Although the expansion and cardiac differentiation of hPSCs as suspension aggregates in scalable platforms are thoroughly studied , examples of neural induction under these conditions are rare, and derivation of NP cells from hPSCs is usually performed under static conditions . Recent work has demonstrated that inhibition of Activin/Nodal and bone morphogenetic protein (BMP) signaling directs hPSCs into neuroectoderm, while blocking signals for mesoderm and endoderm .…”
Section: Discussionmentioning
confidence: 99%
“…Successful expansion of hPSCs in spinner flasks with a working volume up to 100 mL using serum-free media, such as mTeSR1, has been extensively performed [7,9,[12][13][14]. Moreover, scalable 3D aggregate culture systems have also been used for the controlled differentiation of hPSCs although, to date, the majority of protocols has been designed to direct the differentiation towards the cardiac lineage [15][16][17][18]. Still, there is a lack of scalable systems for the controlled neural differentiation of hPSCs.…”
Section: Introductionmentioning
confidence: 99%
“…After 5 days of culture, the hPSC aggregates are 175 ± 25 µm and CM differentiation is then initiated. At 30 days later, 100% of the EBs are beating and up to 90% cTnT+ CM are produced . By optimizing the PSC aggregate size, small molecule concentrations, induction timing, and agitation rate, 1.5–2 × 10 9 hPSC‐CMs are produced in a 1 L spinner flask with a high purity (>90%) .…”
Section: Derivation Of Cms From Pscs For MI Therapymentioning
confidence: 99%